Marine catchment basin effects versus impacts of fisheries on semi-enclosed seas - Caddy, J. F. (ICES journal of marine science, 2000)
Synchronous anthropogenic effects on marine coastal systems, particularly since World War II, make it difficult to separate effects of fishing from terrestrial inputs, especially those caused by nutrient runoff. Natural enrichment is vital to productive fisheries, but over the long term anthropogenic nutrient impacts generally predominate over fishery effects in semi-enclosed seas and affect biodiversity and susceptibility to fishing. Such impacts on marine fisheries beyond natural levels of outflow are referred to here as marine catchment basin (MCB) effects. They require coordinated actions within the catchment area to control them, since fisheries management actions alone are unlikely to be effective in rectifying ecosystem impacts. Net nutrient inflows may be positive or negative, depending on intensity and degree of retention by the receiving marine system and may promote ecosystem change and lead to ecological dominance by exotic species. Initially positive effects of enrichment may disguise the urgent need for coordinated environmental and fishery management measures in semi-enclosed seas. Fisheries impacts are serious, but may be secondary and synergistic, but potentially catastrophic under hypoxic conditions since eutrophic processes make demersal ecosystems particularly sensitive to disturbance of bottom habitats. Hence, fishing with bottom gear may impact bottom fauna and demersal resources within or above organic sediments affected by eutrophic processes and hypoxia. These effects show up as changes in the ratio of pelagic to demersal landings, and support broad-brush comparative studies of areas subject to different levels of environmental impact.